Manipulating pH using near-infrared light assisted by upconverting nanoparticles. Issue 97 (17th October 2016) - Chen, Zhijun; Xiong, Yubing; Etchenique, Roberto; Wu, Si
Abstract : Control of pH was achieved using near-infrared light assisted by upconverting nanoparticles and a ruthenium complex photobase. Abstract : Near-infrared light can be used to manipulate the pH of aqueous solutions by using upconverting nanoparticle-assisted photocleavage of a ruthenium complex photobase. Upconverting nanoparticles and the photobase were also introduced into a pH-responsive hydrogel, in which near-infrared irradiation induced swelling of the hydrogel.